Educating with Alternative Media - Rubí Barquero, José Alberto (2012)
This paper emerges from my interest in exploring ways to transform the daily classroom educational activity into a more pleasant and interesting experience. In this regard, I call attention to the possibilities of cinematography and other audiovisual media as pedagogical means, and the advisability for educators to use them as enhancing alternatives to their professional performance.